DZIELMY SIĘ DOŚWIADCZENIEMSimultaneous myocardial revascularization and aortic valve decalcification in patients operated on for coronary artery disease - Ostrowski, Stanisław; Marcinkiewicz, Anna; Kośmider, Anna; Pawłowski, Witold; Zwoliński, Radosław; Jaszewski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Introduction : Aortic stenosis is the most common acquired cardiac defect. Its prevalence increases with age and among patients above 65 years it occurs in 2-7%. Surgical prosthetic or bioprosthetic valve implantation remains the treatment of choice. Complexity of the surgery is one of the principal operative risk factors. Aim of the study : The aim of this study was to present the re- sults of surgical treatment of patients operated on for coronary artery disease and aortic stenosis, in whom the native valve was preserved, thanks to its debridement. Material and methods : Three patients, aged 69-74, were admitted to the Cardiac Surgery Clinic in Lodz in order to conduct surgical myocardial revascularization. Preoperative echocardiography confirmed co-existence of moderate aortic stenosis (transvalvular maximal gradient 51-59 mm Hg) in each case and good ejection fraction (EF) ranging from 49 to 74%. During surgery, there were firstly aorto-coronary anastomoses implanted. Intraoperative assessment allowed preservation of the aortic valve and decalcification was performed in two cases with additional commissurotomy in one case. The postoperative echocardiography revealed a good effect of the operation (maximal gradient 25-40 mm Hg), which was confirmed to be maintained in the follow-up. In one patient the 5-year follow-up disclosed quite an advanced organic defect without clinical aggravation, which has remained unchanged for the last two years. Conclusions : In asymptomatic or fairly symptomatic patients with moderate aortic stenosis eligible for implantation of aorto-coronary anastomoses, decalcification may be more favorable management. Numerous operative risk factors such as co-morbidities and advanced age should suggest this choice of treatment.